Analisis Pengendalian Piutang Dagang Terhadap Efektifitas Arus Kas Pada PT. Tridjaya Mulia Sukses Manado - Cendra Hiska Mian; Frendy A. O. Pelleng; Joan Mangindaan (JURNAL ADMINISTRASI BISNIS, 2018)
Every company competes to offer a variety of advantages and benefits of products marketed with the aim of making a profit. In the face of such competition, company management must be clever in creating certain bonds between the products it offers to consumers. The purpose of this study was to analyze the control of accounts receivable against cash flow at PT Tridjaya Mulia Sukses Manado whether it was effective. Receivables are a strategy for companies to market products to customers. The company must actually carry out good debt management so that there is no loss. As proposed by Kasmir (2010), prospective customers must meet the requirements known as the 5C principles of Character, Capacity, Capital, Collateral, Condition of Economy. In this study the data used is descriptive research data. Where researchers will describe the object under study by collecting data, recording data, then managing and analyzing the data collected and drawing conclusions. Based on the calculation of the analysis of sales trends, trade receivables, and profit of PT Tridjaya Mulia Sukses is not stable every year because of an increase and decrease. Greater revenue is credit sales rather than cash. Sales on credit will make the companyâ€™s receivables increase. Then the amount of profit in the company also increased due to net sales at the company. Based on the results of the study, the conclusion in this study is that the calculation of PT Tridjaya Mulia Sukses Cash Conversion Cycle in 2013-2017 has not been effective against cash acquisition. The reason is the inhibiting factors such as collection of accounts. It can also be seen that the company has not carried out inventory turnover well as seen from its sales activities and collection of receivables in accordance with the days set by the company, consequently the inventory cycle, receivables, and cash has not run effectively. The cash conversion cycle will get better if the time is shorter. Berdasarkan analisis cash conversion cycle pengendalian piutang dagang PT Tridjaya Mulia Sukses belum efektif karena jumlah piutang yang dimiliki perusahaan belum cukup untuk konversi kas. Based on the cash conversion cycle analysis, PT Tridjaya Mulia Sukses trade receivables control is not effective because the amount of accounts receivable owned by the company in not enough for cash conversion.Â Keywords : Control of Trade Receivables on The Effectiveness of Cash Flow